Hubungan Kadar D-dimer dan C-Reactive Protein terhadap Berat Gejala pada Pasien COVID-19 - Sang Ayu Nyoman Putri Pradnyasari; Moulid Hidayat; Prima Belia Fathana (Faculty of Medicine Universitas Mataram, 2022)
Background: Coronavirus disease 19 (COVID-19) is an acute respiratory infectious disease by SARS-CoV-2. This disease was discovered in Wuhan, China. In some cases, COVID-19 can be life-threatening due to an uncontrolled inflammatory phase characterized by increased levels of D-dimer and C-reactive protein (CRP) in the body. This condition can lead to complications such as ARDS, shock, and even death. This study aims to determine the relationship between D-dimer and CRP levels with the disease severity in COVID-19 patients at the Mataram University Hospital. Methods: This study is an observational analytic study with a cross-sectional design. Data collection took place in March-May 2022 at the Mataram University Hospital. Subjects were selected using consecutive sampling methods through medical record data. The statistical test used the Chi-square and Mann-Whitney comparative tests. Results: A total of 64 subjects were selected, of which 48 subjects underwent a D-dimer examination and 58 underwent a CRP examination. Most subjects were in the age group 18-59 years (64.1%), with the male gender (56.3%). There were 10 subjects (20.8%) had normal D-dimer levels, and 38 subjects (79.2%) had elevated D-dimer levels. Normal CRP levels were found in 6 subjects (10.3%), and 52 subjects (89.7%) had elevated CRP levels. The results of the bivariate test analysis showed p-value = 0.002 for D-dimer levels with severe symptoms, and CRP levels with severe symptoms showed p-value = 0.02. Conclusion: There is a significant correlation statistically and clinically between D-dimer and C-reactive protein levels with the disease severity in COVID-19 patients.